Production, Quality Analysis, and Application of Solid Organic Fertilizer from Household Organic Waste Using Takakura Method on the Growth of Zea mays - Hidayah, Wardatul; Wulandari, Diepa Febriana; Alkas, Taufiq Rinda; Sardianti, Andi Lelanovita; Pratiwi, Wike; Isra, Nur; Maruf, Shalehuddin Denny; Suparjo, Suparjo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Garbage is a serious environmental problem, especially in urban areas. If organic waste is not processed, it will experience uncontrolled decomposition which can produce dangerous gases and leachate that pollute the environment. This study aimed to produce and evaluate the quality of solid organic fertilizer derived from household organic waste using the Takakura method and to determine its effect on the growth of maize (Zea mays). Fertilizer quality was analyzed based on pH, C-organic content, and macronutrients, including nitrogen (N), phosphorus (P), and potassium (K). The fertilizer was used on maize crops by utilizing a completely random approach with three different types of planting media. The growth factors measured included the height of the plants, leaf count, and leaf surface area at 21 and 28 days post-planting. Findings indicated that the solid organic fertilizer possessed a pH of 8.51, an organic carbon content of 0.8%, and a total macronutrient level (N + P₂O₅ + K₂O) of 1.79%, which fell short of the national quality guidelines for solid organic fertilizers. Nevertheless, the application of solid organic fertilizer improved maize growth compared to the control treatment, particularly in the P2 treatment, which showed the best results in terms of leaf number and leaf area. These findings indicate that solid organic fertilizer produced using the Takakura method has potential to be utilized as a soil conditioner and as a supporting input for plant growth.